Study of the Mental Health of the Elderly and Related Factors - Sakineh Gerayllo; Najmeh Shahini; Somayeh Ghorbani; Behzad ghabel (Journal of Social Behavior and Community Health)
Background: Aging and increase in the elderly population are the most important issues in recent years in developed countries and some developing countries. Mental health is one of the crucial aspects of elderly well-being and must be addressed to improve community health. This study is conducted to examine the mental health of the elderly and the related factors in Gorgan city, 2022. Methods: The present study is descriptive-analytical and was conducted using a two-stage cluster random sampling method. First, four comprehensive health service centers were selected as a cluster from among the centers of Gorgan city, and then 263 people were randomly selected from the chosen centers, proportionate to the number of registered elderly individuals in the electronic service system. The standard depression questionnaire for the elderly was utilized for assessment. Data were then entered into SPSS software version 18 and with descriptive and analytical statistical tests, including the Mann-Whitney test, Chi-square test, and logistic regression (The significance level was less than 0.05(. Results: A total of 263 elderly people were evaluated with a mean age of 68.64 ± 7.2 . 143 (54.4%) were male and 120 (45.6%) were female. The prevalence of depression was reported to be 27.8. The occurrence of depression was significantly associated with age, marital status, and the presence of underlying disease conditions (p < 0.05). However, gender, place of residence, and BMI did not show a statistically significant relationship with the occurrence of depression. Aging, underlying diseases, and not being married increase the chance of depression in the elderly. Conclusion: Although the prevalence of depression in the elderly is lower than the average of the whole country in this study, they are in a better condition. However, due to the fact that they are a special target group, as well as the various risk factors of the disease, including age, lack of marriage, and the presence of an underlying disease in this group, it is suggested that more appropriate planning be done to improve their mental health status